Bilateral lower second molar impaction in teenagers: An emergent problem - Shinohara, Elio H. [UNESP]; Kaba, Shajadi Carlos Pardo; Pedron, Irineu Gregnanin; Imparato, José Carlos Petorossi (Wolters Kluwer, 2010)
The frequency of simultaneously impacted second and third molars in teenagers is increasing and becoming a common occurrence in adolescent oral surgery practice. The traditional treatment is the removal of the third molar by conventional access but repositioning of the surgical flap to the distal face of the first molar can predispose to complications such as pericoronitis and delayed healing of the attached gingiva. We present a case in which we use the germectomy approach to remove the impacted third molar for the eruption of the second molar through a vestibular incision. This incision offers excellent bone exposure and exit route for the third molar without disturbing the gingiva attached architecture on the distal face of the first molar providing good healing environment.
Keywords: Impacted teeth; mandible; oral surgery; adolescent; case report; gingiva; human; methodology; molar tooth; pathology; tooth disease; tooth eruption; tooth extraction; tooth flora; Adolescent; Gingiva; Humans; Mandible; Molar; Molar, Third; Tooth Eruption; Tooth Extraction; Tooth Germ; Tooth, Impacted